Architektura w poszerzonym polu - Vidler, Anthony; Lipiński, Filip (Artium Quaestiones, 2025)
This text is a translation into Polish of an essay originally published as A. Vidler, “Architecture’s Expanded Field”, in: Architecture Between Spectacle and Use, ed. A. Vidler, Williamstown, MA/New Haven–London 2008, pp. 143–154. This theoretical study looks at the “expanded field” of contemporary architecture, its diverse modes, iterations and combinations with other domains such as sculpture or landscape using the diagrammatic model introduced by Rosalind E. Krauss for her consideration of 20th-century sculpture. Vidler discusses different types of architecture dominant in the last decades of the 20th and the beginning of the 21st century, pointing to the most recently dominant model called “diagram architecture”.